Encapsulation of Jeruju Leaves Ethanol Extract (Acanthus ilicifolius L.) and It's Antiinflammatory Activities Against Carrageenan-Induced Mice - Tarigan, Indra Lasmana; Kharisma, Tiara; Bemis, Restina; Sutrisno, Sutrisno; Latief, Madyawati (Molekul, 2023)
Jeruju (Acanthus ilicifolius) leaves ethanol extract contains flavonoids that function as an antiinflammatory source. So it is necessary to research to increase the utilization of ethanol extract of Acanthus ilicifolius leaves (A. ilicifolius L.) in encapsulations to increase the stability of antiinflammatory chemical compounds. Concentrated dyestuff extracts are often unstable, so they need to be converted into solid form, and one technique that can be done is encapsulation. Encapsulation aims to protect sensitive components of the material and reduce the degradation of active compounds in the material. The research method begins with preparing samples to be extracted with ethanol solvent, extract phytochemical screening tests, validation determination tests for the analysis method of ethanol extract levels of jeruju leaves, encapsulated formulations, encapsulated physics and chemical properties test and anti-inflammatory tests. In this research, the secondary metabolite compounds contained in the ethanol extract of Jeruju Leaves were flavonoids, phenolics, steroids, and saponins. The determination of the validation of the analysis method of ethanol extract levels of jeruju leaves was obtained by measurement using a UV-vis spectrophotometer and obtained extract levels of 1367,831 mg/g. This research used maltodextrin coating material for encapsulation formulation because it has low viscosity in many ratios, high solubility, has no taste. The freeze-dryer method was used in this study because it produces better drying quality than other drying methods. The physical property test was carried out by analysis using FTIR and SEM while the chemical properties of encapsulation obtained the highest yield proportion of 58.81%, and the highest solubility proportion of 98.76%. Anti-inflammatory testing is carried out using male mice as test animals. Anti-inflammatory testing in mice based on the Rat hind paw oedema method. The average percent inhibition of each dose administered is calculated based on the data results. The high average percent inhibition obtained for Diclofenac Na is 80%. In the research Encapsule 1:12, the 120 mg/KgBW dose had a significant percentage of inhibition of 75.55%, with Na Diclofenac dose of 10 mg/KgBW being 80%.